2016
DOI: 10.1186/s40851-016-0046-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative morphology and development of extra-ocular muscles in the lamprey and gnathostomes reveal the ancestral state and developmental patterns of the vertebrate head

Abstract: The ancestral configuration of the vertebrate head has long been an intriguing topic in comparative morphology and evolutionary biology. One peculiar component of the vertebrate head is the presence of extra-ocular muscles (EOMs), the developmental mechanism and evolution of which remain to be determined. The head mesoderm of elasmobranchs undergoes local epithelialization into three head cavities, precursors of the EOMs. In contrast, in avians, these muscles appear to develop mainly from the mesenchymal head … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 51 publications
2
34
0
Order By: Relevance
“…Smaller epithelial clusters have been described within pre‐otic mesoderm in sturgeon (Kuratani et al, ); chicks (Adelmann, ; Jacob et al, ), and several species of mammals (opossum: Fraser, ; Gilbert, ; cat: Gilbert ; human: Gilbert, ), although whether these are homologous with the large chondrichthian head cavities remains uncertain. While the apparent lack of a consistent correlation between the presence of these vesicles and the sites of EOM and branchial muscle development in many species is confounding, the possibility that they are vestiges of an ancient head mesoderm patterning remains under active investigation (Horder, Presley, & Slipka, ; Suzuki, Fukumoto, et al, ).…”
Section: Head Mesoderm Patterning Before the Onset Of Myogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller epithelial clusters have been described within pre‐otic mesoderm in sturgeon (Kuratani et al, ); chicks (Adelmann, ; Jacob et al, ), and several species of mammals (opossum: Fraser, ; Gilbert, ; cat: Gilbert ; human: Gilbert, ), although whether these are homologous with the large chondrichthian head cavities remains uncertain. While the apparent lack of a consistent correlation between the presence of these vesicles and the sites of EOM and branchial muscle development in many species is confounding, the possibility that they are vestiges of an ancient head mesoderm patterning remains under active investigation (Horder, Presley, & Slipka, ; Suzuki, Fukumoto, et al, ).…”
Section: Head Mesoderm Patterning Before the Onset Of Myogenesismentioning
confidence: 99%
“…EOMs are among the most conserved of vertebrate muscle groups with respect to innervation and early molecular signatures (reviewed by: Suzuki, Fukumoto, et al, 2016) although considerable evolutionary changes in attachments to orbital skeletal elements have been described (Young, 2008). There are, of course, some specialized adaptations, such as "heater" EOMs in billfish (e.g., swordfish, marlin) that are enlarged and physiologically modified to provide a thermal warming blanket to the brain (Block, 1986;Block & Franzini-Armstrong, 1988).…”
Section: Loc At I O Ns a N D S P Ec If I Ca T I O N O F Craniofaciamentioning
confidence: 99%
“…In its first two years, comparative morphology and embryology in evolutionary developmental contexts have been major themes of interest (ex. Hirasawa and Kuratani, 2015;Hojo et al, 2015;Tada and Kuratani, 2015;Hayashi et al, 2015;Nakano, 2015;Onai et al, 2015a, b;Oisi et al, 2015;Shigeno et al, 2015;Kaji et al, 2016;Takeuchi et al, 2016;Suzuki et al, 2016;Hirasawa et al, 2016), a clear trend dating to the launch year, as we reported in a previous review (Fukatsu and Kuratani, 2014). Nonetheless, ZL is open to all areas of basic zoology, and many of the top cited and most frequently accessed papers have been from fields other than evo-devo (Holland, 2015;Kishida et al, 2015;Inoue et al, 2015;Mizunami et al, 2015;Hosokawa et al, 2015;Moriyama and Numata, 2015).…”
Section: Introductionmentioning
confidence: 49%
“…Shone et al (2016) evaluated fossil agnathan morphological traits to speculate about an evolutionary sequence in vertebrate gill number. Suzuki et al (2016) referred to placoderm fossil data (Young, 2008) in suggesting that vertebrate extrinsic eye muscles adhere to ancestral anatomical patterns. As a substantive move in embracing paleontological approaches, ZL has invited Robert Jenkins, a specialist in invertebrate paleontology, to join its editorial board.…”
Section: To Enhance Evolutionary Studiesmentioning
confidence: 99%
“…Among the craniofacial muscles, the morphological configuration of the extraocular muscles (EOMs) has been a longstanding challenge in comparative anatomy and evolutionary biology. Besides specialized adaptations, the basic EOM pattern is shared among all vertebrate classes (Noden and Francis-West, 2006;Suzuki et al, 2016;Young, 2008) and includes 4 recti muscles (the superior rectus, the medial rectus, the inferior rectus, and the lateral rectus) and two oblique muscles (superior oblique and inferior oblique) for movement of the eyeball. Most vertebrates have also accessory ocular muscles involved in protecting the cornea (Noden and Francis-West, 2006;Spencer and Porter, 2006): the retractor bulbi, which serves to retract the eye in several groups of vertebrates and the levator palpabrae superioris, which is not directly associated with the eyeball but controls eyelid elevation in mammalian species.…”
Section: Introductionmentioning
confidence: 99%